Mobilization of Stroke Patients to Prevent Decubitus: A Systematic Review - Farid Rivai, Ahmad; Nur Imani, Meli (Jurnal Medisci, 2023)
Stroke is a disease or nerve disorder that occurs suddenly due to impaired blood flow to the brain. Stroke is known to cause various complications including the occurrence of decubitus wounds. Decubitus is one of the most frequent complications experienced by stroke patients. One of the therapies that can be given to prevent these complications is to take mobilization actions. The purpose of this literature review has been to analyze the provision of mobilization measures in stroke patients to prevent decubitus. The search method uses the Mendeley, PubMed, and Google Scholar databases between 2017 and 2021, with the keyword "Mobilization and Patient Stroke and Pressure Sores" obtained from 100 journals, from the Mendeley 82, PubMed 1 and Google Scholar 17 databases, then from these 100 journals a selection was made and 5 articles were obtained that can be reviewed according to the inclusion criteria. Results and Discussion of a review of literature review in 5 articles stated that mobilization measures can prevent decubitus in stroke patients. Mobilization can facilitate circulatory circulation, maintain muscle tone, and maintain and increase joint range of motion. Mobilization can be given to stroke patients with mobilization actions in the form of changes in the right tilt position, left tilt, and changes in tilt position 30 degrees. This position change can be done every 2 hours. The conclusions and recommendations of this literature review suggest that the administration of mobilizing measures is effective in preventing the occurrence of decubitus in stroke patients. For this reason, this research recommendation is that patients with bed rest be mobilized and given olive oil smears.